Population differences in the structure and coloration of great tit contour feathers. (24th October 2014) - Gamero, Anna; Senar, Juan C.; Hohtola, Esa; Nilsson, Jan‐Åke; Broggi, Juli
<x xml:space="preserve">Abstract</x> Contour feathers cover most of the avian body and play critical roles in insulation, social communication, aerodynamics, and water repellency. Feather production is costly and the development of the optimum characteristics for each function may be constrained by limited resources or time, and possibly also lead to trade‐offs among the different characteristics. Populations exposed to different environmental conditions may face different selective pressures, resulting in differences in feather structure and coloration, particularly in species with large geographical distributions. Three resident populations of great tit Parus major L. from different latitudes differed in feather structure and coloration. Individuals from the central population exhibited less dense and longer contour feathers, with a higher proportion of plumulaceous barbs than either northern or southern birds, which did not differ in their feather structure. Ultraviolet reflectance and brightness of the yellow of the contour feathers of the breast was higher for the southern than for the northern population. Birds with greener plumage (higher hue) had less dense but longer feathers, independently of the population of origin. Differences in feather structure across populations appear to be unrelated to the contour feather colour characteristics except for hue. Nutritional and time constraints during molt might explain the pattern of feather structure, whereas varying sexual selection pressure might underlie the coloration patterns observed. Our results suggest that different selective pressures or constraints shape contour feather traits in populations exposed to varying environmental conditions. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 114, 82–91.